2021
DOI: 10.21203/rs.3.rs-829449/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Predictive Value of Systemic Immune-inflammation Index on Bladder Recurrence on Upper Tract Urothelial Carcinoma Outcomes After Radical Nephroureterectomy

Abstract: Background: To assess the prognostic significance of pre-treatment lymphocyte-related systemic inflammatory biomarkers in upper tract urothelial carcinoma (UTUC) patients.Methods: This study included non-metastatic UTUC patients treated at our hospital between 2001 and 2013. The receiver operating characteristic curve was used to obtain the optimal neutrophile-lymphocyte ratio (NLR), platelet-lymphocyte ratio (PLR), and systemic immune-inflammation index (SII). Multivariate logistic regression was performed to… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…After reviewing the title and abstract, articles that did not meet the criteria were eliminated, leaving 17 articles to be read in their entirety. Six studies were finally confirmed, including 3911 UTUC patients in seven cohorts (13)(14)(15)(16)(17)(18). Figure 1 depicts the process of retrieving information.…”
Section: Search Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After reviewing the title and abstract, articles that did not meet the criteria were eliminated, leaving 17 articles to be read in their entirety. Six studies were finally confirmed, including 3911 UTUC patients in seven cohorts (13)(14)(15)(16)(17)(18). Figure 1 depicts the process of retrieving information.…”
Section: Search Resultsmentioning
confidence: 99%
“…All the articles included in the study were published within the past 5 years and were retrospective in nature. Two of the studies (14, 18) had three cohorts in China, two (13,17) in Taiwan China, one (16) in Japan, and one (13) in Europe and the United States. Among the above six articles, there is one article in Chinese (18) and five in English (13)(14)(15)(16)(17).…”
Section: Characteristics Of the Studies Includedmentioning
confidence: 99%
See 2 more Smart Citations
“…It accurately reflects the local immune response and systemic inflammatory status of body ( 11 ). Multiple studies have substantiated the prognostic value of SII in assessing outcomes for various cancer patients, encompassing bladder cancer ( 12 ), cervical cancer ( 11 ), non-small cell lung cancer ( 13 ), colorectal cancer ( 14 ), and gastric cancer ( 15 ). In recent years, SII has emerged as an indicator for detecting chronic inflammatory disease beyond tumors.…”
Section: Introductionmentioning
confidence: 99%